Socialization Of The Empowerment Of The Community In Developing Tourist Villages In The Banda Aceh City - G, Harbiyah; Fitri, Aida; Anam, Budi Safatul; Fatma, Surya (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
The purpose of this community dedication is to broaden the insight of the village apparatus, the communities related to the development of the tourist village, as well as to raise public awareness of the importance of the management of tourist villages. The outputs obtained from the service of this community are (1) the participants, can add knowledge and insight about the importance of the management of tourism that exists in the City of Banda Aceh from various villages spread out. (2) From the results of socialization, participants understand about the purpose of socialisation to empower the villages that have tourist places and socialization ended with a question-answer session, received some questions from the participants and the community in them: (a) How to develop the tourist village in the village? (b) How the role of the government and the apparatus of the village in developing the village towards the village of Tourism? And how startle in managing tourism to be known more widelyKeywords: Tourism Village Development